Making teaching and learning matter transformative spaces in higher education - Summerfield, Judith; Smith, Cheryl C. (Explorations of educational purpose, 2011)
This volume captures the spirit of collaboration and innovation that its authors bring into the classroom, as well as to groundbreaking undergraduate programs and initiatives. Coming from diverse points of view and twenty different disciplines, the contributors illuminate the often perplexing debates about what matters most in higher education today. Each chapter tells a unique story about creating vital pedagogical arenas that have the potential to transform teaching and learning for both faculty and students. These exploratory spaces include courses under construction, cross-college and interdisciplinary collaborations, general education reform initiatives, and fresh perspectives on student support services, faculty development, freshman learning communities, writing across the curriculum, on-line degree initiatives, and teaching and learning centers. All these spaces lend shape to an over-arching, system-wide project bringing together the often disconnected silos of undergraduate education at The City University of New York (CUNY), America?s largest urban public university system. Since 2003, the University's Office of Undergraduate Education has sponsored coordinated efforts to study and improve teaching and learning for the system?s 260,000 undergraduates enrolled at 18 distinct colleges. The contributors to this volume present a broad spectrum of administrative and faculty perspectives that have informed the process of transforming the undergraduate experience. Combined, the voices in these chapters create a much-needed exploratory space for the interplay of ideas about how teaching and learning need to matter in evolving notions of higher education in the twenty-first century. In addition, the text has wider social relevance as an in-depth exploration of change and reform in a large public institution. -Publisher's description.